METODE PAIRED ROLE PLAYING UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA JAWA RAGAM KRAMA - fitri nur hayati (Muhamadiyah, 2018)
AbstractLearning Javanese is a challenge for students from both inside and outside Java (foreign speakers). The purpose of this study was to improve the ability to speak Javanese language using the Paired Role Playing method. This classroom action research uses the Kemmis and Mc.Taggart model which consists of four stages, namely planning, action, observation, and reflection. The subjects of this study were students of class X IPS 1 Muhammadiyah 2 High School Yogyakarta, with 30% of students coming from outside Java. Data collection techniques use observation, tests, and documentation. Data analysis was performed with qualitative and quantitative descriptive analysis techniques. In pre-action, 75% of students did not complete learning, because they were still